Kerakterisasi ZnO Nanorod Yang Disintesis Secara Hydrothermal Dengan Berbagai Konsentrasi Sebagai Nanogenerator - Ali Umar, Marjoni Imamora (Universitas PGRI Sumatera Barat, 2020)
Characterization of zinc oxide (ZnO) nanorod as a nanogenerator synthesized using a hydrothermal method with various concentrations of a growing solution is reported in this article. The concentrations of the ZnO nanorod growing solution used were 0.02, 0.03, 0.04., 0.05, and 0.06M (denoted as Kp0.02, Kp0.03, Kp0.04, Kp0.05, and Kp0.06). The nanogenerator characterization was carried out using AFM Tip conduction (Scanning Probe Microscope in CPII / Veeco). The characterization of ZnO nanorod as a nanogenerator is discussed because it has piezoelectric properties caused by the flexing carried out on the nanorod. The resulting voltage is influenced by the morphology of the ZnO nanorod film, especially the diameter and density of the nanorod. The voltage surge increase with the concentration of growth solution increased. The highest voltage surge produced was 3.33 mV in the Kp0.04 sample.